Penerapan Teknik Behavioral Contract dalam Konseling Kelompok untuk Mengatasi Kebasaan Membolos Siswa Kelas XI SMKN 5 Bantaeng - Masri, Syehrimuliani; Saman, Abdul; Saniasa, Saniasa (Indonesian Journal of School Counseling: Theory, Application, and Development, 2021)
This study aims to: (1) to find out habit of truancy of classXI students of SMK Negeri 5 Bantaeng before being given group counseling services with behavioral contract techniques, (2) to determine of SMK Negeri 5 Bantaeng after being given group counseling services with the behavioral contract technique. The method used is action research in guidance and counseling services. Research result shows that: 1) the results of the analysis before being given group counseling services with behavioral contract techniques, the habit of skipping students on average five group counseling services with behavioral contract techniques, the habit of truant students experienced a decrease that previously averaged five times a month to ance a month.